SYSTEM OPERATING PROCEDURE SEBAGAI REGULASI INTERNAL PENGELOLAAN ZAKAT DI BAZNAS - Hambali, Ahmad; Chandra, Alex; Trisnomurti, Ria; Liwa, Maria Ana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
BAZNAS is a non-structural government institution established under Law No. 23 of 2011 with the aim of managing zakat effectively and efficiently to alleviate poverty and improve the welfare and prosperity of the community. To achieve these strategic objectives, the implementation of professional governance, manifested through adherence to both internal regulations (policies, systems, and procedures) and external regulations (general regulations and norms), plays a crucial role in the growth and development of not only the central BAZNAS but also BAZNAS branches throughout Indonesia. As part of optimizing national zakat governance, BAZNAS continuously improves its zakat management performance by organizing and strengthening systems, procedures, and regulations, especially those governing BAZNAS internally, through their implementation at both the central and regional levels. Strengthening zakat governance, particularly through the implementation of systems and procedures by all BAZNAS, is expected to not only drive the achievement of the target of trustworthy zakat management but also enhance the credibility and trust of the community, especially muzakki (zakat payers) and mustahik (zakat recipients), in paying zakat, infaq, and sadaqah to BAZNAS. Therefore, the central BAZNAS requires a standardized implementation of systems and procedures for regional BAZNAS to be immediately applied in managing zakat in their respective regions. This will be achieved through mentoring and technical training on the implementation of various internal regulations, systems, and procedures for zakat management. The goal is to maximize the implementation of standardized policies, systems, and procedures for zakat management in the regions by mentoring and simulating regional zakat managers to enable them to carry out zakat management more professionally.